Why not kill them all?: the logic and prevention of mass political murder - Chirot, Daniel (Princeton Univ. Press, 2006)
Introduction: Are we killers or peacemakers? -- Why genocides? : are they more common now than in the past? -- The psychological foundations of genocidal killing -- Why is limited warfare more common than genocide? -- Strategies of conflict reduction to decrease the chances of mass political murder in our time -- Conclusions: Our question answered